Non-aqueous electrolyte secondary battery

By using lithium and metal M composite oxide positive electrode active materials with specific composition and particle size range, the problem of insufficient binding force of positive electrode active materials during the charging and discharging process of lithium-ion secondary batteries was solved, achieving high capacity and excellent cycle characteristics.

CN112602212BActive Publication Date: 2025-01-14PANASONIC INTELLECTUAL PROPERTY MANAGEMENT CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN201980053555.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2018-09-28
Filing Date
2019-09-19
Publication Date
2025-01-14
Estimated Expiration
2039-09-19

AI Technical Summary

Technical Problem

In existing lithium-ion secondary batteries, the bonding force between primary particles of the positive electrode active material decreases during charging and discharging, making it difficult to simultaneously achieve high cycle performance and high capacity.

Method used

A composite oxide containing lithium and a metal M other than lithium is used as the positive electrode active material, wherein the metal M contains at least nickel and aluminum or manganese, the atomic ratio of nickel to metal M Ni/M is greater than 0.8 and less than 1.0, and the average particle size of the primary particles is greater than 0.20 μm and less than 0.35 μm. The bonding force between the primary particles is improved by adjusting the calcination conditions and composition.

Benefits of technology

It improves the cycle characteristics and high capacity of lithium-ion secondary batteries, suppresses the fragmentation and isolation of positive electrode active materials, and enhances the energy density and stability of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN112602212B_ABST
    Figure CN112602212B_ABST
Patent Text Reader

Abstract

The non-aqueous electrolyte secondary battery comprises: a positive electrode containing a positive electrode active material, a negative electrode containing a negative electrode active material, and a non-aqueous electrolyte. The positive electrode active material comprises a composite oxide containing lithium and a metal M other than lithium, and a plurality of primary particles of the composite oxide are aggregated to form secondary particles. The metal M comprises at least nickel and aluminum and / or manganese, and the atomic ratio of nickel to the metal M is Ni / M greater than 0.8 and less than 1.0. The average particle size of the primary particles is greater than 0.20 μm and less than 0.35 μm.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a nonaqueous electrolyte secondary battery. Background Art

[0002] A non-aqueous electrolyte secondary battery represented by a lithium-ion secondary battery comprises a positive electrode, a negative electrode and a non-aqueous electrolyte, wherein the positive electrode contains a lithium-containing composite oxide as a positive electrode active material. As the lithium-containing composite oxide, for example, lithium nickelate is used, which is advantageous for high capacity, and a part of the nickel is replaced with a different metal such as aluminum (Patent Document 1).

[0003] Prior art literature

[0004] Patent Literature

[0005] Patent Document 1: Japanese Patent Application Publication No. 2017-226576 Summary of the invention

[0006] In the positive electrode active material, multiple primary particles of lithium composite oxide are usually aggregated to form secondary particles. As the positive electrode active material expands and contracts during charge and discharge, the binding force between the primary particles decreases, and the secondary particles break at the primary particle interface, which intensifies the isolation of the primary particles and sometimes reduces the cycle characteristics.

[0007] On the other hand, as electronic devices and the like have become more advanced in performance, nonaqueous electrolyte secondary batteries used as power sources thereof have been required to have higher capacities and improved cycle characteristics.

[0008] In view of the above situation, one aspect of the present invention relates to a non-aqueous electrolyte secondary battery, comprising: a positive electrode comprising a positive electrode active material, a negative electrode comprising a negative electrode active material, and a non-aqueous electrolyte, the positive electrode active material comprising a composite oxide containing lithium and a metal M other than lithium, a plurality of primary particles of the composite oxide aggregated to form secondary particles, the metal M comprising at least nickel and aluminum and / or manganese, the atomic ratio Ni / M of the nickel relative to the metal M being greater than 0.8 and less than 1.0, and the average particle size of the primary particles being greater than 0.20 μm and less than 0.35 μm.

[0009] According to the present invention, a nonaqueous electrolyte secondary battery having a high capacity and excellent cycle characteristics can be obtained. BRIEF DESCRIPTION OF THE DRAWINGS

[0010] Figure 1 This is a schematic perspective view in which a part of a nonaqueous electrolyte secondary battery according to one embodiment of the present invention is cut away. DETAILED DESCRIPTION

[0011] The nonaqueous electrolyte secondary battery described in the embodiment of the present invention comprises: a positive electrode containing a positive electrode active material, a negative electrode containing a negative electrode active material, and a nonaqueous electrolyte. The positive electrode active material comprises a composite oxide containing lithium and a metal M other than lithium, and a plurality of primary particles of the composite oxide are aggregated to form secondary particles. The metal M contains at least nickel (Ni) and contains aluminum (Al) and / or manganese (Mn), and the atomic ratio of nickel to metal M Ni / M is greater than 0.8 and less than 1.0. The average particle size of the primary particles is greater than 0.20 μm and less than 0.35 μm.

[0012] When the above-mentioned structure is satisfied, the reduction of the binding force between the primary particles accompanying the expansion and contraction of the positive electrode active material during charge and discharge is suppressed, and the fragmentation of the primary particle interface of the secondary particles and the isolation of the primary particles accompanying this are suppressed. As a result, the cycle characteristics are improved. In addition, a high capacity (initial capacity) can be obtained.

[0013] When Ni / M is 0.8 or more, the amount of Ni is large and a high capacity can be obtained. However, when Ni / M is 1, the metal M does not contain Al and Mn, so the cycle characteristics are deteriorated.

[0014] By making the metal M contain Al and / or Mn, the bonding force between primary particles is improved. It can be considered that the composite oxide containing at least one of Al and Mn and Li present near the surface of the primary particles helps to improve the bonding force between primary particles. Al and Mn are also advantageous in terms of thermal stability.

[0015] When the average particle size of the primary particles of the positive electrode active material (composite oxide) is greater than 0.20 μm and less than 0.35 μm, excellent cycle characteristics are obtained while having high capacity. When the average particle size of the primary particles exceeds 0.35 μm, the absolute amount of expansion and contraction of the primary particles accompanying charge and discharge becomes larger. Therefore, even if the composite oxide (metal M) contains Al and Mn, the binding force between the primary particles becomes insufficient, and the cycle characteristics are easily reduced. On the other hand, when the average particle size of the primary particles is less than 0.20 μm, the growth of the crystal is insufficient, and the part that does not contribute to the charge and discharge reaction increases. Therefore, the capacity is easily reduced, and the cycle characteristics are also easily reduced.

[0016] The average particle size of primary particles of the positive electrode active material is determined as follows.

[0017] A scanning electron microscope (SEM) is used to obtain a cross-sectional image of the positive electrode active material. For example, the positive electrode is embedded in a resin, and a cross-section of the positive electrode mixture layer is formed by cross-section polishing (CP) processing, and the cross-section is photographed using an SEM. Alternatively, the powder of the positive electrode active material can be embedded in a resin, and a cross-section of the positive electrode active material particles is formed by cross-section polishing (CP) processing, and the cross-section is photographed using an SEM. From the obtained image, 1 to 3 secondary particles are randomly selected, and more than 100 primary particles are randomly selected therefrom, and the equivalent circular diameter is calculated using image analysis, and the average particle size of the primary particles is calculated based on the obtained equivalent circular diameters.

[0018] Specifically, the circle equivalent diameter D of the kth primary particle is obtained by image analysis. k Assume that the kth primary particle is D k / 2 as the radius of the sphere, the volume V of the primary particle is calculated using the following formula k .

[0019] V k =(4π / 3)×(D k / 2) 3

[0020] The volumes V1, V2, ..., V1 obtained for n (n is an integer greater than or equal to 100) primary particles are used. n , use the following formula to calculate the volume average value V a .

[0021] Volume average V a =(ΣV k ) / n

[0022] Where, ΣV k =V1+V2+···+V n .

[0023] The obtained volume average V a The average particle size D of the primary particles is calculated using the following formula: a .

[0024] Average particle size D a =2×(3 / 4π×V a ) 1 / 3

[0025] From the viewpoint of obtaining stable cycle characteristics, the dispersion degree of the particle size of the primary particles of the positive electrode active material is preferably 5% or less. In order to make the above dispersion degree less than 5%, it is ideal that: during the heating process of calcination in the production of the positive electrode active material, the temperature is raised under relatively mild conditions (e.g., a heating rate of 2 to 5°C / min).

[0026] The degree of dispersion of the particle size of primary particles is determined as follows.

[0027] The volumes V1, V2, ..., V obtained for n primary particles in the process of determining the average particle size of the primary particles are used. n and the volume average V a , the dispersion V is calculated using the following formula v .

[0028] Dispersion V v =(1 / n)×Σ(V k -V a ) 2

[0029] In the formula, Σ(V k -V a ) 2 =(V1-V a ) 2 +(V2-V a ) 2 +···+(V n -V a ) 2 .

[0030] Using the dispersed V v , use the following formula to calculate the standard deviation S v .

[0031] Standard DeviationS v =(V v ) 1 / 2

[0032] Using the standard deviation S obtained above v and the volume average V a , the degree of dispersion is calculated using the following formula.

[0033] Dispersion degree = (S v / V a ) 1 / 3 ×100

[0034] Preferably, the proportion of Al and / or Mn on the surface side (interface) is larger than that on the internal side of the primary particle. At this time, a large amount of composite oxides containing at least one of Al and Mn and Li are present at the interface of the primary particle, and the binding force between the primary particles is efficiently improved. At this time, the hardness inside the primary particle and the binding force at the surface (interface) of the primary particle can be obtained with a good balance, and the cycle characteristics are further improved.

[0035] By the method for producing a positive electrode active material described below, the proportion of the presence of Al and / or Mn in the surface portion side can be made larger than that in the inner side of the primary particles. Such a concentration gradient of Al and Mn in the primary particles can be confirmed by, for example, energy dispersive X-ray spectroscopy (EDX). The above concentration gradient is likely to occur when a large amount of Al and Mn is used (for example, when Al / M is 0.04 or more or when Mn / M is 0.01 or more).

[0036] When the metal M contains Al, the atomic ratio of Al to the metal M, Al / M, is preferably 0.04 or more and 0.07 or less. When Al / M is 0.04 or more, the binding force between the primary particles of the positive electrode active material is further improved, and the cycle characteristics are further improved. When Al / M is 0.07 or less, the capacity is further increased.

[0037] When the metal M contains Mn, the atomic ratio of Mn to the metal M, Mn / M, is preferably 0.01 or more and 0.07 or less. When Mn / M is 0.01 or more, the binding force between the primary particles of the positive electrode active material is further improved, and the cycle characteristics are further improved. When Mn / M is 0.07 or less, the capacity is further increased.

[0038] When the metal M contains Al and Mn, the atomic ratio of the sum of Al and Mn to the metal M, (Al + Mn) / M, is preferably 0.01 or more and 0.15 or less.

[0039] In addition to containing Ni, Al, and Mn, the metal M may contain other metals. The other metals include, for example, at least one selected from the group consisting of Co, Mg, Fe, Cu, Zn, Cr, Ti, Nb, Zr, V, W, Ta, Mo, Si, and B. From the viewpoint of improving the cycle characteristics, among them, the other element is preferably Co.

[0040] The composite oxide is, for example, a rock salt type composite oxide having a layered structure, and can be represented by Li a Ni 1-b Al b O2, Li a Ni 1-c Mn c O2, Li a Ni 1-d-e-f Co d Al e Mn f O2, etc. by a general formula. Here, 0.9 ≤ a ≤ 1.2, 0 < b ≤ 0.2, 0 < c ≤ 0.2, 0 < e + f, 0 < d + e + f ≤ 0.2. It should be noted that the value of a representing the amount of Li is, for example, the value in a battery in a discharged state (state of charge: SOC is 0%), and increases or decreases due to charge and discharge.

[0041] As a method for preparing a positive electrode active material (a composite oxide containing lithium and a metal M other than lithium), there can be cited a method in which, for example, a lithium compound is mixed with a compound containing metal M obtained by a coprecipitation method, and the resulting mixture is roasted under specified conditions. Aluminum oxide and / or manganese oxide powders can be further added to the mixture. It is easy to distribute Al and / or Mn in large quantities at the interface of the primary particles. As lithium compounds, lithium hydroxide, lithium carbonate, etc. can be cited. As compounds containing metal M, hydroxides containing metal M, oxides containing metal M, etc. can be cited. In the positive electrode active material obtained by the above-mentioned preparation method, secondary particles obtained by agglomerating multiple primary particles are formed.

[0042] The average particle size (D50) of the secondary particles of the positive electrode active material is, for example, 5 μm or more and 20 μm or less. It should be noted that the average particle size (D50) mentioned here refers to the median particle size when the volume cumulative value reaches 50% in the volume-based particle size distribution. The average particle size (D50) of the secondary particles is obtained by measuring the particle size distribution using a laser diffraction method.

[0043] The average particle size of the primary particles of the positive electrode active material can be adjusted by changing, for example, the calcination conditions (calcination temperature, calcination time, etc.). The calcination time is, for example, 5 hours or more and 20 hours or less. The calcination temperature is, for example, 650° C. or more and 850° C. or less. The calcination is preferably performed in an oxygen atmosphere (for example, an oxygen concentration of 30% or more).

[0044] The composition of the positive electrode active material can be adjusted by, for example, changing the composition of the compound containing the metal M.

[0045] Generally, the cycle characteristics of a battery are dominated by the degradation of the positive electrode. On the other hand, the primary particles in the positive electrode active material have a high binding force to each other, so the degradation of the positive electrode is significantly suppressed. Therefore, the cycle characteristics of the battery may be affected by slight degradation of the negative electrode. At this time, in order to further improve the cycle characteristics, it is important to improve the negative electrode and suppress degradation. In this regard, when the negative electrode active material contains graphite, by making the BET specific surface area of ​​the graphite 2m 2 / g or less, the side reactions at the negative electrode are reduced and the cycle characteristics are further improved.

[0046] The BET specific surface area of ​​graphite is 2m 2 When the negative electrode has a surface area of ​​1000 nm and a surface area of ​​1000 nm, the degradation caused by the side reaction of the negative electrode is suppressed, so the utilization rate of the positive electrode active material is increased. Generally speaking, if the utilization rate of the positive electrode active material increases, the expansion and contraction of the positive electrode active material increases, and there is a tendency for the positive electrode to be easily degraded due to the decrease in the binding force between the primary particles.

[0047] On the other hand, in the present invention, for the positive electrode active material, by using a composite oxide of a specific composition and making the average particle size of the primary particles within a specific range, the binding force between the primary particles is increased, and the positive electrode degradation caused by the reduction of the binding force between the primary particles is suppressed. 2 The combination with graphite having an average carbon content of 0.1 wt% or less can further improve the cycle characteristics specifically.

[0048] The positive electrode includes, for example, a positive electrode current collector and a positive electrode mixture layer supported on the positive electrode current collector and containing a positive electrode active material. 3 The positive electrode mixture layer may contain 3.2 g or more of the positive electrode active material. In this case, a battery having excellent cycle characteristics and a higher energy density can be obtained.

[0049] Generally speaking, if the amount of positive electrode active material contained in the positive electrode mixture layer is 3 If the amount in the positive electrode mixture layer exceeds 3.2 g, the stress generated in the positive electrode mixture layer increases as the positive electrode active material expands and contracts during charge and discharge, and the secondary particles are easily broken at the primary particle interface, which easily reduces the cycle characteristics.

[0050] In contrast, in the present invention, for the positive electrode active material, by using a composite oxide of a specific composition and making the average particle size of the primary particles within a specific range, the bonding strength between the primary particles of the positive electrode active material is improved. 3 When the amount in the positive electrode mixture layer is 3.2 g or more, the secondary particles are also suppressed from breaking at the primary particle interface, and the cycle characteristics are improved.

[0051] Hereinafter, the structure of the nonaqueous electrolyte secondary battery will be described in detail.

[0052] (positive electrode)

[0053] The positive electrode comprises, for example, a positive electrode current collector and a positive electrode mixture layer formed on the surface of the positive electrode current collector. The positive electrode mixture layer can be formed by applying a positive electrode slurry obtained by dispersing the positive electrode mixture in a dispersion medium to the surface of the positive electrode current collector and drying it. The dried coating film can be rolled as needed. The positive electrode mixture layer can be formed on one surface of the positive electrode current collector or on both surfaces. The positive electrode mixture contains a positive electrode active material as an essential component, and as an optional component, can contain a binder, a conductive agent, a thickener, etc.

[0054] As the binder, resin materials such as fluororesins such as polytetrafluoroethylene and polyvinylidene fluoride (PVDF); polyolefin resins such as polyethylene and polypropylene; polyamide resins such as aramid resins; polyimide resins such as polyimide and polyamide-imide; acrylic resins such as polyacrylic acid, polymethyl acrylate, and ethylene-acrylic acid copolymers; vinyl resins such as polyacrylonitrile and polyvinyl acetate; polyvinyl pyrrolidone; polyether sulfone; rubber-like materials such as styrene-butadiene copolymer rubber (SBR), etc. These can be used alone or in combination of two or more.

[0055] Examples of the conductive agent include graphites such as natural graphite and artificial graphite; carbon blacks such as acetylene black; conductive fibers such as carbon fibers and metal fibers; carbon fluoride; metal powders such as aluminum; conductive whiskers such as zinc oxide and potassium titanate; conductive metal oxides such as titanium oxide; organic conductive materials such as phenylene derivatives, etc. These may be used alone or in combination of two or more.

[0056] Examples of thickeners include carboxymethyl cellulose (CMC) and modified products thereof (including salts such as Na salts), cellulose derivatives such as methyl cellulose (cellulose ethers, etc.), saponified products of polymers having vinyl acetate units such as polyvinyl alcohol, polyethers (polyalkylene oxides such as polyethylene oxide), etc. These may be used alone or in combination of two or more.

[0057] As the positive electrode current collector, a non-porous conductive substrate (metal foil, etc.) or a porous conductive substrate (mesh, grid, punched metal sheet, etc.) can be used. As the material of the positive electrode current collector, for example, stainless steel, aluminum, aluminum alloy, titanium, etc. can be exemplified. The thickness of the positive electrode current collector is not particularly limited, and is, for example, 3 to 50 μm.

[0058] The dispersion medium is not particularly limited, and examples thereof include water; alcohols such as ethanol; ethers such as tetrahydrofuran; amides such as dimethylformamide; N-methyl-2-pyrrolidone (NMP); or mixed solvents thereof.

[0059] (negative electrode)

[0060] The negative electrode includes, for example, a negative electrode current collector and a negative electrode mixture layer formed on the surface of the negative electrode current collector. The negative electrode mixture layer can be formed by applying a negative electrode slurry obtained by dispersing the negative electrode mixture in a dispersion medium to the surface of the negative electrode current collector and drying it. The dried coating can be rolled as needed. The negative electrode mixture layer can be formed on one surface of the negative electrode current collector or on both surfaces. The negative electrode mixture contains a negative electrode active material as an essential component, and as an optional component, it can contain a binder, a conductive agent, a thickener, etc. As a binder, a thickener and a dispersion medium, the substances exemplified in the positive electrode can be used. In addition, as a conductive agent, in addition to using graphite, the substances exemplified in the positive electrode can be used.

[0061] Examples of negative electrode active materials include carbon materials, silicon compounds such as silicon and silicon oxide, and lithium alloys containing at least one selected from the group consisting of tin, aluminum, zinc, and magnesium. Examples of carbon materials include graphite (natural graphite, artificial graphite, etc.), amorphous carbon, etc.

[0062] As the negative electrode current collector, a non-porous conductive substrate (metal foil, etc.), a porous conductive substrate (mesh, grid, punched metal sheet, etc.) can be used. As the material of the negative electrode current collector, stainless steel, nickel, nickel alloy, copper, copper alloy, etc. can be exemplified. The thickness of the negative electrode current collector is not particularly limited, and from the viewpoint of balancing the strength and lightness of the negative electrode, it is preferably 1 to 50 μm, and more preferably 5 to 20 μm.

[0063] (Separator)

[0064] Usually, it is desirable to sandwich a separator between the positive electrode and the negative electrode. The separator has high ion permeability and has appropriate mechanical strength and insulation. As the separator, a microporous film, a woven fabric, a non-woven fabric, etc. can be used. As the material of the separator, polyolefins such as polypropylene and polyethylene are preferred.

[0065] As an example of the structure of a non-aqueous electrolyte secondary battery, an electrode group formed by winding a positive electrode and a negative electrode across a separator and a structure obtained by containing a non-aqueous electrolyte in an outer package can be listed. Alternatively, an electrode group of other forms such as a stacked electrode group formed by stacking a positive electrode and a negative electrode across a separator can also be used to replace the wound electrode group. The non-aqueous electrolyte secondary battery can be any form such as a cylindrical type, a square type, a coin type, a button type, a laminated type, etc.

[0066] Figure 1 This is a schematic perspective view showing a partially cutaway portion of a rectangular nonaqueous electrolyte secondary battery according to an embodiment of the present invention.

[0067] The battery comprises a square-bottomed battery case 4, an electrode group 1 and a non-aqueous electrolyte (not shown) contained in the battery case 4. The electrode group 1 comprises a long strip-shaped negative electrode, a long strip-shaped positive electrode, and a separator sandwiched therebetween to prevent direct contact. The electrode group 1 is formed by winding the negative electrode, the positive electrode and the separator around a flat winding core as the center and pulling out the winding core.

[0068] One end of the negative electrode lead 3 is mounted on the negative electrode collector of the negative electrode by welding or the like. The other end of the negative electrode lead 3 is electrically connected to the negative terminal 6 provided on the sealing plate 5 by means of a resin insulating plate (not shown). The negative terminal 6 is insulated relative to the sealing plate 5 by means of a resin gasket 7. One end of the positive electrode lead 2 is mounted on the positive electrode collector of the positive electrode by welding or the like. The other end of the positive electrode lead 2 is connected to the back of the sealing plate 5 by means of an insulating plate. That is, the positive electrode lead 2 is electrically connected to the battery case 4 which also serves as the positive terminal. The insulating plate separates the electrode group 1 from the sealing plate 5 and separates the negative electrode lead 3 from the battery case 4. The outer edge of the sealing plate 5 is fitted into the open end of the battery case 4, and the fitting portion is laser welded. In this way, the opening of the battery case 4 is sealed by the sealing plate 5. The injection hole for the non-aqueous electrolyte provided in the sealing plate 5 is blocked by the sealing plug 8.

[0069] Example

[0070] Hereinafter, the present invention will be specifically described based on Examples and Comparative Examples, but the present invention is not limited to the following Examples.

[0071] 《Examples 1 to 3, Comparative Examples 1 to 2》

[0072] (1) Preparation of positive electrode active material

[0073] The Ni obtained by coprecipitation 0.82 Co 0.15 Al 0.03 (OH)2 and Li2CO3 are mixed in such a way that the atomic ratio of Li to the sum of Ni, Co and Al is Li / (Ni+Co+Al) of 1.05 / 1, and calcined in an oxygen atmosphere to obtain a positive electrode active material (composite oxide). The heating rate during the heating process during calcination is set to be less than 5°C / min. The composition of the positive electrode active material is Li 1.05 Ni 0.82 Co 0.15 Al 0.03 O2. It should be noted that the composition of the positive electrode active material was determined by ICP emission spectrometry.

[0074] (2) Preparation of positive electrode

[0075] The positive electrode active material, acetylene black and polyvinylidene fluoride were mixed in a mass ratio of 100:2:2, and N-methyl-2-pyrrolidone (NMP) was added, and then stirred using a mixer (manufactured by PRIMIX, TKHIVIS MIX) to prepare a positive electrode slurry. The positive electrode slurry was applied to the surface of the aluminum foil, and after the coating was dried, it was rolled to form a positive electrode mixture layer (density of 3.6 g / cm 3 )'s positive electrode.

[0076] (3) Preparation of negative electrode

[0077] The negative electrode active material, sodium carboxymethyl cellulose (CMC-Na) and styrene-butadiene rubber (SBR) were mixed in a mass ratio of 100:1:1, and after adding water, a mixer (manufactured by PRIMIX, TKHIVIS MIX) was used to stir to prepare a negative electrode slurry. The negative electrode slurry was applied to the surface of the copper foil, and after the coating was dried, it was rolled to form a negative electrode mixture layer (density of 1.7 g / cm 3 ) negative electrode. The negative electrode active material used has a BET specific surface area of ​​1.4 m 2 / g of graphite powder (average particle size: 20 μm).

[0078] (4) Preparation of non-aqueous electrolyte

[0079] LiPF6 was dissolved in a mixed solvent of ethylene carbonate (EC) and diethyl carbonate (DEC) (volume ratio of 1:1) at a concentration of 1.6 mol / L to prepare a non-aqueous electrolyte.

[0080] (5) Fabrication of non-aqueous electrolyte secondary batteries

[0081] One end of the aluminum positive electrode lead is mounted on the positive electrode obtained above. One end of the nickel negative electrode lead is mounted on the negative electrode obtained above. A wound electrode body is made by winding the positive electrode and the negative electrode through a polyethylene separator. After the electrode body is vacuum dried at 105°C for 2 hours, it is placed in a bottomed cylindrical battery case that also serves as the negative terminal. The battery case uses an iron case (outer diameter of 18 mm and height of 65 mm). Next, after injecting a non-aqueous electrolyte into the battery case, the opening of the battery case is sealed using a metal sealing body that also serves as the positive terminal. At this time, a resin gasket is sandwiched between the sealing body and the open end of the battery case. The other end of the positive lead is connected to the sealing body, and the other end of the negative lead is connected to the inner bottom surface of the battery case. In this way, a cylindrical non-aqueous electrolyte secondary battery of type 18650 is made.

[0082] In the preparation of the above positive electrode active material, positive electrode active materials a1 to a3, b1 to b2 having average primary particle diameters of the values ​​shown in Table 1 were obtained. The average primary particle diameters of the positive electrode active materials were obtained by the above method. The average primary particle diameters of the positive electrode active materials were adjusted by adjusting the Ni 0.82 Co 0.15 Al 0.03 The calcination temperature of the mixture of (OH)2 and Li2CO3 is changed within the range of 700°C to 800°C and the calcination time is changed within the range of 5 hours to 10 hours. The average particle size (D50) of the secondary particles of the positive electrode active materials a1 to a3 and b1 to b2 obtained by the above method is about 12 μm.

[0083] The dispersion degree of the particle size of the primary particles of the positive electrode active materials a1 to a3 obtained by the above method is about 1%. When the distribution of Al in the primary particles of the positive electrode active materials a1 to a3 is investigated using energy dispersive X-ray spectroscopy (EDX), it can be confirmed that the presence ratio of Al on the surface side (interface of the primary particles) is larger than that on the internal side of the primary particles.

[0084] Using the positive electrode active materials a1 to a3 and b1 to B2, nonaqueous electrolyte secondary batteries A1 to A3 and B1 to B2 were produced.

[0085] The following evaluations were performed on each of batteries A1 to A3 and B1 to B2.

[0086] [evaluate]

[0087] (A) Initial capacity

[0088] <Charge>

[0089] In an environment of 25°C, constant current charging was performed at a current of 0.2C until the voltage reached 4.2V, and then constant voltage charging was performed at a voltage of 4.2V until the current reached 0.02C. After charging, a rest period of 20 minutes was allowed.

[0090] Discharge

[0091] After the rest, the battery was discharged at a constant current of 0.2 C at 25°C until the voltage reached 2.5 V, and the initial discharge capacity (initial capacity) was determined. The initial capacity was expressed as an index with the initial capacity of battery B1 of Comparative Example 1 being 100.

[0092] (B) Capacity maintenance rate

[0093] <Charge>

[0094] At 45°C, the battery was charged at a constant current of 0.5C until the voltage reached 4.3 V. After charging, the battery was allowed to rest for 20 minutes.

[0095] Discharge

[0096] After resting, the battery was discharged at a constant current of 0.5C at 45°C until the voltage reached 2.5V.

[0097] The above-described charge and discharge are repeated to determine the discharge capacity C1 at the first cycle and the discharge capacity C2 at the 500th cycle.

[0098] The capacity retention rate was calculated from the following formula using the discharge capacity C1 and the discharge capacity C2 obtained above.

[0099] Capacity retention rate (%) = (discharge capacity C2 / discharge capacity C1) × 100

[0100] (C) Resistance change rate

[0101] The charge and discharge of the above (B) was performed for one cycle. Thereafter, constant current charging was performed at a current of 0.2C at 25°C until the voltage reached 4.2V. After constant current charging, constant voltage charging was performed at a voltage of 4.2V until the current reached 0.02C. In this way, a battery with a SOC of 100% was obtained.

[0102] After charging, the battery was rested for 20 minutes and then discharged at a constant current of 0.5 C. The difference ΔV between the voltage immediately before the start of discharge and the voltage 10 seconds after the start of discharge was divided by the current I (ΔV / I) and was taken as the DC resistance R1.

[0103] A separately manufactured battery was prepared, and the charge and discharge in the above (B) were performed for 500 cycles. Thereafter, the battery was charged and discharged in the same manner as above, and ΔV / I was determined as the DC resistance R2.

[0104] The resistance change rate was calculated using the DC resistance R1 and the DC resistance R2 obtained above using the following formula.

[0105] Resistance change rate (%) = (DC resistance R2 / DC resistance R1) × 100

[0106] 《Examples 4 to 6, Comparative Examples 3 to 4》

[0107] The Ni obtained by coprecipitation 0.82 Co 0.13 Al 0.05(OH)2 and Li2CO3 are mixed in such a way that the atomic ratio of Li to the sum of Ni, Co and Al is Li / (Ni+Co+Al) of 1.05 / 1, and calcined in an oxygen atmosphere to obtain a positive electrode active material (composite oxide). The heating rate during the heating process during calcination is set to be less than 5°C / min. The composition of the positive electrode active material is Li 1.05 Ni 0.82 Co 0.13 Al 0.05 O2.

[0108] In the preparation of the above positive electrode active material, positive electrode active materials a4 to a6, b3 to b4 having average primary particle diameters of the values ​​shown in Table 1 were obtained. The average primary particle diameter of the positive electrode active material was obtained by the above method. The average primary particle diameter of the positive electrode active material was adjusted by adjusting the Ni 0.82 Co 0.13 Al 0.05 The calcination temperature of the mixture of (OH)2 and Li2CO3 was changed within the range of 700°C to 800°C and the calcination time was changed within the range of 5 hours to 10 hours. The average particle size (D50) of the secondary particles of the positive electrode active materials a4 to a6 obtained by the above method was about 12 μm.

[0109] The particle size dispersion of the primary particles of the positive electrode active materials a4 to a6 obtained by the above method was about 1%. EDX confirmed that the presence ratio of Al on the surface side (primary particle interface) of the primary particles of the positive electrode active materials a4 to a6 was greater than that on the inside.

[0110] Batteries A4 to A6 and B3 to B4 were prepared and evaluated in the same manner as in Example 1 except that positive electrode active materials a4 to a6 and b3 to b4 were used instead of positive electrode active material a1.

[0111] Table 1 shows the evaluation results of batteries A1 to A6 and B1 to B4.

[0112] [Table 1]

[0113]

[0114] For the positive electrode active material, batteries A1 to A6 with Ni / M of 0.8 or more and less than 1 and an average primary particle size of 0.2 μm or more and 0.35 μm or less can obtain high initial capacity, high capacity retention rate and low resistance change rate. In batteries A1 to A6, the fragmentation of the primary particle interface of the secondary particles accompanying repeated charge and discharge is suppressed.

[0115] In batteries B1 and B3 where the average primary particle size of the positive electrode active material exceeded 0.35 μm, the absolute amount of expansion and contraction of the primary particles accompanying charge and discharge became large, and the bonding force between the primary particles became insufficient, so the capacity retention rate decreased and the resistance change rate increased.

[0116] In batteries B2 and B4 in which the average particle size of primary particles of the positive electrode active material was less than 0.2 μm, the crystal growth of the primary particles was insufficient, and thus the initial capacity decreased.

[0117] 《Example 7》

[0118] The Ni obtained by coprecipitation 0.82 Co 0.12 Mn 0.06 (OH)2 and Li2CO3 were mixed in such a way that the atomic ratio of Li to the sum of Ni, Co and Mn was Li / (Ni+Co+Mn) of 1.05 / 1, and the positive electrode active material a7 was prepared in the same manner as in Example 1. The composition of the positive electrode active material is Li 1.05 Ni 0.82 Co 0.12 Mn 0.06 O2.

[0119] The average particle size of the primary particles of the positive electrode active material a7 obtained by the above method is 0.35 μm. The average particle size (D50) of the secondary particles of the positive electrode active material a7 obtained by the above method is about 12 μm. The degree of dispersion of the particle size of the primary particles of the positive electrode active material a7 obtained by the above method is about 1%. It can be confirmed by EDX that the presence ratio of Mn on the surface side (interface of the primary particles) is larger than that on the internal side of the primary particles of the positive electrode active material a7.

[0120] Battery A7 was produced and evaluated in the same manner as in Example 1 except that positive electrode active material a7 was used instead of positive electrode active material a1. Table 2 shows the evaluation results of batteries A1, A4, and A7.

[0121] [Table 2]

[0122]

[0123] Compared with the battery A1 in which Al / M was less than 0.04, the battery A4 in which Al / M was 0.04 or more and 0.07 or less could obtain a high capacity retention rate and a low resistance change rate.

[0124] In the battery A7 in which Mn / M was 0.01 or more and 0.07 or less, a high initial capacity, and a high capacity retention rate and a low resistance change rate at the same level as those of the battery A4 were obtained.

[0125] 《Examples 8-9》

[0126] Batteries A8 and A9 were prepared and evaluated in the same manner as in Example 1 except that graphite powder having a BET specific surface area shown in Table 3 was used as the negative electrode active material.

[0127] 《Examples 10-11》

[0128] Batteries A10 and A11 were prepared and evaluated in the same manner as in Example 4 except that graphite powder having a BET specific surface area shown in Table 3 was used as the negative electrode active material.

[0129] Table 3 shows the evaluation results of Batteries A1 and A4 and Batteries A8 to A11.

[0130] [Table 3]

[0131]

[0132] The BET specific surface area of ​​the negative electrode active material is 2.0 m 2 / g or less in batteries A1 and A8, the BET specific surface area of ​​the negative electrode active material exceeds 2.0 m 2 / g compared with the battery A9, a high capacity retention rate and a low resistance change rate can be obtained.

[0133] The BET specific surface area of ​​the negative electrode active material is 2.0 m 2 / g or less in batteries A4 and A10, the BET specific surface area of ​​the negative electrode active material exceeds 2.0 m 2 / g compared with the battery A11, a higher capacity retention rate can be obtained.

[0134] Industrial Applicability

[0135] The nonaqueous electrolyte secondary battery of the present invention is suitable for use as a main power source for portable electronic devices or the like, or as a power storage device (for example, a storage device for natural energy such as sunlight).

[0136] Description of Reference Numerals

[0137] 1 Electrode set

[0138] 2 Positive lead

[0139] 3 Negative lead

[0140] 4 Battery housing

[0141] 5 Sealing plate

[0142] 6 Negative terminal

[0143] 7 Gasket

[0144] 8 Sealing plug

Claims

1. A non-aqueous electrolyte secondary battery comprising: a positive electrode containing a positive electrode active material, a negative electrode containing a negative electrode active material, and a non-aqueous electrolyte, The positive electrode active material includes a composite oxide containing lithium and a metal M other than lithium, A plurality of primary particles of the composite oxide are aggregated to form secondary particles. The metal M contains at least nickel and aluminum and / or manganese, When the metal M includes the aluminum, the atomic ratio of aluminum to the metal M (Al / M) is greater than or equal to 0.04 and less than or equal to 0.07; when the metal M includes the manganese, the atomic ratio of manganese to the metal M (Mn / M) is greater than or equal to 0.01 and less than or equal to 0.07, The atomic ratio Ni / M of the nickel to the metal M is greater than or equal to 0.8 and less than 1.0, The average particle size of the primary particles is 0.20 μm or more and 0.35 μm or less, The positive electrode comprises a positive electrode current collector and a positive electrode mixture layer supported on the positive electrode current collector and containing the positive electrode active material. The positive electrode mixture layer has a 3 The positive electrode mixture layer contains 3.2 g or more of the positive electrode active material. The negative electrode active material comprises graphite, and the BET specific surface area of ​​the graphite is 2 m 2 / g or less.

2. The nonaqueous electrolyte secondary battery according to claim 1, wherein The aluminum and / or manganese are present in a larger proportion on the surface side than on the inner side of the primary particle.

Citation Information

Patent Citations

  • Lithium-nickel-containing composite oxide and nonaqueous electrolyte secondary battery

    JP2017226576A

  • Positive electrode active material for nonaqueous electrolyte secondary battery and manufacturing method therefor, and nonaqueous electrolyte secondary battery

    JP2010080394A

  • Positive electrode active material for lithium ion secondary battery, positive electrode for lithium ion secondary battery arranged by use thereof, and lithium ion secondary battery

    JP2016076470A

  • Carbonous coated graphite particles for lithium ion secondary battery negative electrode material, method for manufacturing the same, lithium ion secondary battery negative electrode, and lithium ion secondary battery

    JP2018092916A

  • Composite positive active material, method of preparing the same, positive electrode including the composite positive active material, and lithium battery including the positive electrode

    US20170179470A1